Parapneumonic Effusions and Empyema - TETİKKURT, Cüneyt (Cerrahpaşa Medical Journal, 2014)
Parapneumonic pleural effusions present a difficult diagnostic and therapeutic challenge for the clinician. The spectrum ranges from a small pleural effusion that responds to antibiotic therapy to empyema with systemic infection. Today the physicians must be aware of the development of an parapneumonic effusion because the treatment failure mostly depends on the delay in diagnosis and instituting proper therapy. While simple parapneumonic effusions are easily managed with antibiotic treatment alone complicated effusions may require surgical interventions like tube thoracostomy, thoracoscopy or open drainage. This chapter reviews the current approach to parapneumonic pleural effusions.The clinical course, classification system for parapeumonic effusions, diagnostic and guidelines for the treatment of various stages of the pleural infection are described.